Flood Governance and Spatial Planning Failures in Batu City: A Socio-Legal Study on Risk Mitigation - Moh. Muhibbin; Slamet Muchsin; Riswandha Imawan; Ahmad Bastomi (Administrative and Environtmental Law Review, 2025)
Flooding remains a persistent threat in Indonesian urban areas, including Batu City, East Java, causing extensive physical, social, and economic impacts. This study examines flooding impacts and analyzes prevention and mitigation efforts from a socio-legal perspective, with a focus on governance and spatial planning. Using a qualitative sociological-legal approach, the study finds that recurrent flooding in Batu City is primarily driven by human-induced land-use changes and weak enforcement of spatial planning regulations. Conversion of protected forests into agricultural land and settlements has reduced water catchment capacity, while degradation of the Brantas River Basin, including sedimentation and river narrowing, exacerbates flood risk. Batu, Junrejo, and Bumiaji sub-districts are the most affected, with flood durations often exceeding three hours. The findings indicate that deficiencies in spatial planning governance and law enforcement are key institutional factors in flood vulnerability. This study contributes to environmental administrative law by linking spatial governance failures to disaster risk and offers policy recommendations for revising the Regional Spatial Plan (RTRW) and strengthening local flood mitigation regulations.